Unsuspected choledochal lithiasis - Matteucci, Pablo; Barreiro, Claudia; del Campo (h), Alberto; Consoni, Carlos (Cirugía del Uruguay, 1994)
The choledocolithiasis unsuspected has descended its incidence to figures below 5% in world literature. The autors study its frecuency in'a serie of 101 cholecistectomies. A cholangiography study was practised in 76 of them, and 4 cases of choledocolithiasis were found.